Case study on resilience and desistance of adolescent offenders - Goh, Siew Lan. (2008)
The objective of this research was to study the recovery or resilience process in adolescent offenders. The research adopted a case study methodology. Comparisons were made amongst four cases, of which two of them were adolescents who had recovered from previous delinquent behaviour and two others were adolescents who persisted in delinquent behaviour despite being convicted in the court of law. The research found that the familial factors, such as positive relationship with at least one parent, were important protective factors that contributed to resilience. There was also evidence that showed that individual protective factors, such as self-esteem; internal locus of control; optimism, and having personal goals, could contribute to resilience. The findings suggested that resilience could be strengthened in the non-resilient adolescent, so that the adolescent offenders could become resilient or desistant in the future.